2000
DOI: 10.1080/135457000337679
|View full text |Cite
|
Sign up to set email alerts
|

Working Time as Gendered Time

Abstract: Household-labor time and market-labor time are organized in part through the social structure of unequal gender relations. Generally, women do more household work than men, women's market work is undervalued, and the greatest rewards for market work accrue to men. The career model of employment is biased in favor of men who have few household responsibilities. Even noncareer seniority-sensitive job paths assume male incumbency with limited competition from household responsibilities. In this article we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 18 publications
1
74
0
1
Order By: Relevance
“…For example, masculine family roles (i.e., provider) and the role of ideal worker (e.g., being constantly available to the employer) are interdependent and complementary; whereas feminine family roles (i.e., available nurturer) and the role of ideal worker are independent and conflicting (Simon, 1995). Women often experience roles that are incompatible, which increases the stress of pursuing work and family roles for them (Duxbury & Higgins, 1991;Simon, 1995;Sirianni & Negrey, 2000;Williams, 2000). Some studies using Western samples have found no gender differences in experiencing family-work conflict, although women report interference from work to family more than men (Duxbury, Higgins, & Lee, 1994;Frone, Russell, & Cooper, 1992b;Gutek, Searle, & Klepa, 1991).…”
Section: Literature Reviewmentioning
confidence: 95%
“…For example, masculine family roles (i.e., provider) and the role of ideal worker (e.g., being constantly available to the employer) are interdependent and complementary; whereas feminine family roles (i.e., available nurturer) and the role of ideal worker are independent and conflicting (Simon, 1995). Women often experience roles that are incompatible, which increases the stress of pursuing work and family roles for them (Duxbury & Higgins, 1991;Simon, 1995;Sirianni & Negrey, 2000;Williams, 2000). Some studies using Western samples have found no gender differences in experiencing family-work conflict, although women report interference from work to family more than men (Duxbury, Higgins, & Lee, 1994;Frone, Russell, & Cooper, 1992b;Gutek, Searle, & Klepa, 1991).…”
Section: Literature Reviewmentioning
confidence: 95%
“…While this is an advantage for them at the time of recruitment, it delays their promotion and their capacity to negotiate for a higher salary or benefits and stock options. The dominant model of career growth require linearity and continuity in work (Papanek, 1973) and career interruptions because of childcare commitments are found to disadvantage women (Sirianni & Negrey, 2000). Not surprisingly, internationally, the majority of women are employed in routine and specialist work while men are engaged in analytical and managerial activities (Ahuja, 2002).…”
Section: Mobility Of Gso Work and Mobility Restrictions On Womenmentioning
confidence: 99%
“…This is not done because they are incompetent but because it puts less stress on themselves and their families. (Frome, Alfeld, Eccles, & Barber, 2006;Wajcman, 2013;Sirianni & Negrey, 2000). Beinomugisha, Kamya and Said (2014) indicated that one of the perceptions that exists about women in management is that they are unstable workers.…”
Section: International Journal Of Social Science Researchmentioning
confidence: 99%